Impaired Baroreflex Sensitivity after Bilateral Convulsive Seizures in Patients with Focal Epilepsy - Hampel, Kevin G.; Elger, Christian E.; Surges, Rainer (Frontiers in Neurology, 2017)
BACKGROUND: Sudden unexpected death in epilepsy (SUDEP) is probably due to an autonomic failure in the early postictal phase after bilateral convulsive seizures (BCS) in the majority of cases. The baroreflex sensitivity (BRS) is an established and reliable biomarker of autonomic function and sudden cardiac death. OBJECTIVE: To investigate whether postictal BRS depends on seizure type. METHODS: Beat-to-beat systemic blood pressure and heart rate were continuously and non-invasively recorded with the ccNexfin® device in patients with focal epilepsy undergoing video-EEG monitoring. BRS was calculated using the sequence as well as the spectral method. A random mixed linear model was applied to analyze the influence of seizure type on BRS during three different time periods of 15-minutes length each (interictal, preictal and postictal). In addition, the possible effects of other factors (hypertension, hemispheric lateralization of ictal activity, epilepsy type, body position, vigilance state) were explored. Data are given as median with interquartile range. RESULTS: A total of 26 seizures of 26 patients were analyzed. In BCS (n=7), BRS significantly dropped from a preictal value of 15.0 ms/mm Hg (13.0 to 19.4) and an interictal value of 15.6 ms/mm Hg (12.0 to 20.4) to 3.1 ms/mm Hg (2.7 to 10.5) during the postictal period (p<0.0001) according to the sequence method. This finding was replicated with the spectral method. In contrast, focal seizures (n=19) did not lead to significant alterations of BRS in the postictal phase. CONCLUSION: Postictal BRS depends on the seizure type and is markedly impaired after BCS. The present study provides further evidence for a disturbed autonomic function following BCS. These findings might be related to cardiovascular failure in the context of SUDEP.